2022
DOI: 10.3390/ijms232113482
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Promotes Skeletal Muscle Regeneration by Regulating miR-221/222

Abstract: Genistein (GEN), a phytoestrogen, has been reported to regulate skeletal muscle endocrine factor expression and muscle fiber type switching, but its role in skeletal muscle regeneration is poorly understood. As a class of epigenetic regulators widely involved in skeletal muscle development, microRNAs (miRNAs) have the potential to treat skeletal muscle injury. In this study, we identified miR-221 and miR-222 and their target genes MyoG and Tnnc1 as key regulators during skeletal muscle regeneration, and both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, it is well known that isoflavones play a positive role in skeletal muscle growth and regeneration, in addition to their antioxidant and anti-inflammation effects. 16–18,45,51–54 Although our previous study used alcohol extract, it was observed through metabolomics analysis that the fermented soybean extract had a higher level of isoflavone metabolites than the unfermented one. 17 In this study, since FYK was used without an additional extraction process, it is thought that it contributed to the alleviation of muscle atrophy due to the large amount of physiologically active ingredients it contains, including metabolites previously found in the fermented soybean extract, as well as water-soluble amino acids that are beneficial for physiological activities.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it is well known that isoflavones play a positive role in skeletal muscle growth and regeneration, in addition to their antioxidant and anti-inflammation effects. 16–18,45,51–54 Although our previous study used alcohol extract, it was observed through metabolomics analysis that the fermented soybean extract had a higher level of isoflavone metabolites than the unfermented one. 17 In this study, since FYK was used without an additional extraction process, it is thought that it contributed to the alleviation of muscle atrophy due to the large amount of physiologically active ingredients it contains, including metabolites previously found in the fermented soybean extract, as well as water-soluble amino acids that are beneficial for physiological activities.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in skeletal muscle cells, genistein downregulates the expression of the micro-RNA miR-222, which is characteristically increased in muscle atrophy [ 143 ]. This mechanism can lead to muscle regeneration and regulation of muscle fiber type [ 144 , 145 ]. Finally, the isoflavone derived from licorice, glabridin, is able to reduce protein degradation and promote glucose uptake in skeletal muscle cells [ 146 , 147 ].…”
Section: Interaction Between Phenolic Compounds and Microbiota: Possi...mentioning
confidence: 99%